2003
DOI: 10.1046/j.1542-474x.2003.08105.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of QT Dispersion and Localized QT Difference to Coronary Pathology in a Population with Unstable Coronary Artery Disease

Abstract: QTd in ischemia seems to be increased by a mechanism unrelated to localization and severity of coronary disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In this study, they reported that although some patients had myocardial perfusion abnormalities, none of the patients had obstructive epicardial coronary disease, supporting the suggestion of microvascular abnormalities. Previous studies concerning QT dispersion in coronary artery disease have shown that QT dispersion increased in case of myocardial ischemia [27, 28]. So, SCD-associated myocardial ischemia may also cause an increase in QT dispersion.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, they reported that although some patients had myocardial perfusion abnormalities, none of the patients had obstructive epicardial coronary disease, supporting the suggestion of microvascular abnormalities. Previous studies concerning QT dispersion in coronary artery disease have shown that QT dispersion increased in case of myocardial ischemia [27, 28]. So, SCD-associated myocardial ischemia may also cause an increase in QT dispersion.…”
Section: Discussionmentioning
confidence: 96%